Sulfadoxine–pyrimethamine alone or with azithromycin for the intermittent preventive treatment of malaria in pregnancy: protocol for a systematic review and meta-analysis - Halidou Tinto; Innocent Valea; Sékou Samadoulougou; Hermann Sorgho; Toussaint Rouamba; Moussa Lingani; Serge Ouoba; Maïmouna Sanou (BMJ Open)
Introduction Increasing Plasmodium resistance levels to sulfadoxine–pyrimethamine (SP) threaten the effectiveness of intermittent preventive treatment in pregnancy (IPTp) and have prompted the evaluation of alternative strategies. Azithromycin (AZ) could have add-on effects on malaria and treat sexually transmitted infections (STIs), both conditions described as major causes of adverse pregnancy outcomes (APO). Inconsistent findings on the utility of AZ for the prevention of APO were reported; however, thus far, no comprehensive meta-analytic synthesis of data has been published. This review aims to investigate the effects of SP+AZ administered in women as IPTp on the risk of low birth weight in malaria-endemic areas.Methods and analysis Eligible studies will be identified through a pre-established search strategy in several electronic databases (Medline, Cochrane Library, Web of Science, EMBASE, WHO International Clinical Trials Registry Platform, ClinicalTrials.gov and AJOL) and will comprise peer-reviewed papers reporting original data on the effects of SP+AZ on the risk of APO. Only randomised controlled trials published until 30 September 2024 in English or French will be included. IPTp with SP+AZ regimens (intervention) will be compared with IPTp with SP alone or with a placebo (control). As primary outcomes, data on the frequency of low birth weight will be collected. Secondary outcomes include the rates of stillbirth, preterm birth, miscarriage and neonatal death. Data will be extracted independently by two reviewers using a predefined extraction form. If the data quality allows for quantitative synthesis, a fixed-effects meta-analysis will be conducted if there is low inter-study heterogeneity. Otherwise, the random-effects meta-analysis will be conducted to take into account uncertainty in pooled estimates that could be due to inter-study heterogeneity. The review protocol was designed according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses Protocols (PRISMA-P) guidelines.Ethics and dissemination Ethical clearance is not needed as the data will be from already published studies in which informed consent and ethical approval were obtained by primary investigators. Our dissemination plan includes the publication in a peer-reviewed journal as well as conference presentations.PROSPERO registration number CRD42020149592.